Disruption of the hepcidin/ferroportin regulatory circuitry causes low axial bone mass in mice - Ledesma-Colunga, Maria G.; Baschant, Ulrike; Fiedler, Imke A. K.; Busse, Björn; Hofbauer, Lorenz C.; Muckenthaler, Martina; Altamura, Sandro; Rauner, Martina (Bone, 2020)
Ferroportin (FPN) is the only known iron exporter. Mutations conferring resistance of FPN to hepcidin-mediated degradation cause the iron overload disorder hereditary hemochromatosis type 4. While iron overload is associated with low bone mass, the mechanisms involved are not completely understood. Here, we aimed to investigate whether the disruption in the hepcidin/FPN axis in Fpn(c326s) mice and subsequent systemic iron accumulation impacts on bone tissue to a similar extent as in Hfe(-/-) mice, which are hallmarked by a milder iron overload phenotype. Hfe(-/-) and Fpn(c326s) mice show increased plasma iron levels and liver iron content, whereas iron overload was more pronounced in Fpn(c326s) compared to Hfe(-/-) mice. Bone volume fraction and trabecular thickness at the femur were not different between 10 and 14-week-old male wild-type (WT), Hfe(-/-) and Fpn(c326s) mice. By contrast, both Hfe(-/-) and Fpn(c326s) mice exhibited a lower bone volume fraction [Hfe(-/-), 24%; Fpn(c326s) 33%; p < 0.05] and trabecular thickness [Hfe(-/-), 10%; Fpn(c326s) 15%; p < 0.05] in the fourth lumbar vertebra compared to WT mice. Analysis of the bone formation rate at the tibia showed no difference in both genotypes, but it was reduced in the vertebral bone of Fpn(c326s) [36%, p < 0.05] compared to WT mice. Serum levels of the bone formation marker, P1NP, were significantly reduced in both, Hfe(-/-) and Fpn(c326s) compared with WT mice [Hfe(-/-), 35%; Fpn(c326s) 40%; p < 0.05]. Also, the intrinsic differentiation capacity of Fpn(c326s) osteoblasts was impaired. Osteoclast parameters were not grossly affected. Interestingly, the liver iron content and plasma iron levels negatively correlated with the bone formation rate and serum levels of P1NP. Thus, disruption of the hepcidin/ferroportin regulatory axis in Fpn(c326s) mice results in axial bone loss due to suppressed bone formation.
Gesehen am 03.08.2020